On the Interaction of Existential Rules and Equality Constraints in Ontology Querying - Calì, A; Gottlob, G; Orsi, G; Pieris, A (2012)
Ontological query processing is an exciting research topic in database theory, knowledge representation, and logic programming. In many cases, ontological constraints are expressed over an extensional database by extending traditional Datalog rules to allow existential quantification and equality atoms in the head. The unrestricted use of these features causes undecidability of query answering and, therefore, their interaction must be controlled. This work provides a tutorial-like introduction to the problem of query answering under existential and equality constraints. We survey the most notable (semantic and syntactic) restrictions to such constraints ensuring decidability of query answering, and we discuss their practical application to conceptual modelling.